Design of joint provision of tailings and clearence in Yauricocha mine - Ortiz Sánchez, Oswaldo (2011)
The feasibility of co-disposal of tailing and clearance is been evaluated in Yauricocha Mine, for which one it is been studied the involved variables such as cut and compression resistance, permeability, density, particle size, chemical composition for tailing and clearance of the mine, leaching facility of minerals in both, influence of seismic acceleration in the stability of tailing and clearance’s slopes. It was found that the most stable mixture from a physical and chemical point of view is three of clearance to one of tailing (3C/1T). The safety factor calculated by the Bishop algorithm SLIDE, is above 1.1 in pseudo-static conditions. In addition, there were evaluated more forms of joint storage for clearance-tailing, concluding that for the Yauricocha conditions, it can be used injections of thickened tailings through perforated pipes placed in the advancing front of the landfill. The injection can be prepared in clearing layers of 2.4 m of thickness on the pipe.